Modelling Flood Wave Propagation as a Result of Dam Piping Failure Using 2D-HEC-RAS - Mahmood J. Mohamed; Ibtisam R. Karim; Mohammed Y. Fattah; Nadhir Al-Ansari (Salehan Institute of Higher Education, 2023)
In recent years, there has been a serious request for innovative, accurate approaches to be determined and controlled for dam failures. The present study aims to explore and evaluate the flood wave parameters that result from a dam break due to piping failure occurring in the body of the dam and routing the flood waves. Mosul Dam, which lies in the north of Iraq, and a reach of the Tigris River downstream the dam to Samarra Barrage at about 470 km are selected as a case study. A two-dimensional Hydrologic Engineering Center River Analysis System (2D HEC-RAS) and the Geographic Information System (GIS) have been supposed to be suitable for development calculations of the flood wave parameters based on the Digital Elevation Model (DEM) and land cover satellite images that enhance the calculations. The reservoir and two-dimensional flow area are delineated and incorporated with DEM. Manning`s coefficient for the whole area has been extracted according to the Land Cover satellite image, which showed that its value ranges between 0.025 to 0.037 with a correlation coefficient R2equal to 0.845 and 0.801 for the calibration and validation processes, respectively. The results of the scenario display a substantial performance of the maps produced from the model that represented the depth, velocity, and water surface elevation. All the maximum values of dam break parameters lie near the dam body and slightly decrease downstream. It is pre-eminent that the 2D HEC-RAS model is appropriate for analyzing and simulating the occurrence of dam breaches by visualizing the distribution of flood wave depth and velocities in two dimensions. Hence, the clear improvement in producing maps, which monitor the spread of hydrodynamic waves, gives an indication of risk areas that are threatened by inundation and aids in the formulation of emergency plans. Doi: 10.28991/CEJ-2023-09-10-010 Full Text: PDF